FAKTOR-FAKTOR YANG MEMENGARUHI PENYELENGGARAAN HUTAN KOTA: STUDI KASUS KOTA MEDAN, DELI SERDANG DAN PALANGKA RAYA - Elvida Yosefi Suryandari; Iis Alviya (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
Most of urban infrastructure development have been increasing while the existing urban forest is inadequate for fulfilling the needs of urban communities. The purpose of this study is to determine the factors affecting the implementation of urban forest in the cities of Medan, Deli Serdang and Palangka Raya. The study used weighing and stakeholder analysis. Weighing is done through ranking of the factors that affect urban forest such as aspects of biophysical, socio-economic, organizational and policy, all based on the perception of the respondents. The results showed that the most influencing factors are scarcity of urban forest land and land disputes. Increasing urban population causes the increasing demand for residential and its supporting facilities, which in turn will reduce urban forest area. On the other hand, forestry policy failed to foster implementation of urban forest because this concept has not been understood by local government as the executor. Another obstacle is the lack of budget and its continuity. Efforts to overcome the scarcity of urban forest land is by optimazing urban forest management through species enrichment and plantings on idle land. Coordination and collaboration among stakeholders are needed in regional planning, budgeting and stipulation of district regulation to reduce the risk of land use conversion.